Physical properties of sintered stainless steel 17-4PH micro-part processed by micro-powder injection molding - Abu Bakar Sulong; Nashrah Hani Jamadon; Norhamidi Muhamad; Al Basir (Penerbit Universiti Kebangsaan Malaysia, 2022)
Micro-powder injection molding (μPIM) is a modification of powder injection molding (PIM) process and a globally recognized manufacturing process route that can be used largely to produce sophisticated micro-sized components using a wide range of metals and ceramics. The demand of μPIM process is currently increasing in various applications in telecommunication, electronics, aerospace, biomedical, and automotive industries. In this research work, sintering at three different temperatures between 1250 °C and 1350 °C at a heating rate of 10 °C/min with a dwelling period of 3 h on micro-injection molded and debound (solvent and thermal) micro-sized components of stainless steel 17-4PH (SS 17-4PH) was carried out. After the sintering operation, defect-free SS 17-4PH micro-specimens were achieved. The relative density, which is referred to as an important physical property of SS 17-4PH micro-parts, increased substantially from 95.3% to 97.5% when the sintering temperature was enhanced from 1250 °C to 1350 °C. The maximum shrinkage of 12.9% was observed in micro-sized specimens at the sintering temperature of 1350 °C. After the completion of sintering process, the findings revealed that SS 17-4PH micro-parts can be produced successfully on the grounds of μPIM process employing the SS 17-4PH feedstock with powder loading of 69 vol.%.